2012
DOI: 10.1007/s10327-012-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic diversity in the web blight pathogen Thanatephorus cucumeris (anamorph = Rhizoctonia solani) subgroups AG-1-IE and AG-1-IF with molecular markers

Abstract: genetic diversity in the web blight pathogen Thanatephorus cucumeris (anamorph = Rhizoctonia solani) subgroups AG-1-IE and AG-1-IF with molecular markers" (2012). Papers in Plant Pathology. 273. http://digitalcommons.unl.edu/plantpathpapers/273 Abstract Web blight, an important foliar disease of dry beans in the Americas, is a challenge to manage. We studied genetic variation of 92 isolates of Rhizoctonia solani subgroups AG-1-IE and AG-1-IF using DNA fingerprinting methods and mycelial compatibility grouping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
7
13
0
Order By: Relevance
“…This finding was in agreement with previous reports of variation at the ITS1 region of R. solani isolates within AGs (Justesen et al 2003;Gonzalez et al 2012). However, Gonzalez et al (2012) included a greater number of isolates per site and observed intragroup variation when analysing the rDNA-ITS sequence. However, Gonzalez et al (2012) included a greater number of isolates per site and observed intragroup variation when analysing the rDNA-ITS sequence.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding was in agreement with previous reports of variation at the ITS1 region of R. solani isolates within AGs (Justesen et al 2003;Gonzalez et al 2012). However, Gonzalez et al (2012) included a greater number of isolates per site and observed intragroup variation when analysing the rDNA-ITS sequence. However, Gonzalez et al (2012) included a greater number of isolates per site and observed intragroup variation when analysing the rDNA-ITS sequence.…”
Section: Discussionsupporting
confidence: 93%
“…Low levels of variability in ITS sequences of AG1-IE and AG-1IF isolates from Latin America and the Caribbean have been reported by Godoy-Lutz et al (2008). Moreover, their results were in agreement with the analysis based on URP and ISSR molecular markers and mycelial compatibility (Gonzalez et al 2012). Moreover, their results were in agreement with the analysis based on URP and ISSR molecular markers and mycelial compatibility (Gonzalez et al 2012).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Worldwide, 14 AGs and numerous subgroups have been identified based on physical, chemical, pathogenic and molecular characteristics. Isolates can exist as multinucleate homokaryons or heterokaryons and present diverse mating strategies (homothallic or heterothallic) (González et al, 2012). Phaseolus vulgaris isolates belong mainly to AG 1 (6 subgroups), AG 2 (4 subgroups) and AG 4 (Carling, 1996;Schneider et al, 1997;Carling et al, 1999;Carling et al, 2002;Godoy-Lutz et al, 2003;GodoyLutz et al, 2008;González et al, 2006).…”
Section: Introductionmentioning
confidence: 99%